Rainwater harvesting system for academic building. Is it worth it? / Azirah Adnan, Asmalia Che Ahmad and Suharto Teriman - Azirah, Adnan; Che Ahmad, Asmalia; Teriman, Suharto (2021)
Rainwater Harvesting System (RWHS) is proposed to address the water scarcity problem and as an alternative water supply for non-potable water usage. However, the economic benefit of the system depends on site-specific criteria such as rainfall availability, catchment area, storage, and water demand. This paper attempts to evaluate the economic benefits of RWHS for toilet flushing usage for one academic building at Politeknik Sultan Azlan Shah (PSAS) namely the Civil Engineering Department (CED) block. Daily rainfall data employed in this work were obtained from the nearest rainfall station at Felda Gedangsa and the water demand was obtained from the building's occupants through a questionnaire survey combined with data obtained from PSAS's documents. The daily water mass balance model was adopted as the simulation approach. The economic benefits of RWHS in terms of percentage of reliability (R) and payback period (PBP) were examined for the academic block. In addition, the effects of two types of rainwater tank sizes on PBP were also evaluated. The tanks are High-Density Polyethylene (HDPE) tank and Fibre-reinforced Plastic (FRP) sectional tanks. It was found that the percentage of reliability (R) for Civil Engineering Department block is between 82.22% to 100% by using a tank with a size ranging from 10 m3 to 150 m3. Interestingly, for tanks with a size range up to 60 m3, the cost of a HDPE tank is lower than FRP sectional tanks with the PBP ranging from 11 to 19 years and 13 to 20 years, respectively. However, for tanks with a size of 100 m3 onwards, the cost of HDPE tank becomes more expensive than the cost of FRP sectional tank with PBP ranging from 23 to 38 years and 23 to 29 years, respectively.